A Nationwide Survey and Multicenter Registry-Based Database of Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy in Japan - Shindo, Akihiro; Tabei, Ken-ichi; Taniguchi, Akira; Nozaki, Hiroaki; Onodera, Osamu; Ueda, Akihiko; Ando, Yukio; Urabe, Takao; Kimura, Kazumi; Kitagawa, Kazuo; Hanyu, Haruo; Hirano, Teruyuki; et al. (Frontiers in Aging Neuroscience, 2020)
Objectives Clinical characteristics of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) include migraine, recurrent stroke, white matter lesions, and vascular dementia. CADASIL is one of the most common hereditary cerebral small vessel diseases. Clinical presentation of CADASIL varies and a racial gap may exist between the Asian and Caucasian populations. This is the first nationwide epidemiological survey which aimed to elucidate the clinical features of CADASIL in Japan. Moreover, the registration database of CADASIL was constructed. Methods Subjects included CADASIL patients who visited the hospitals (totally 1,448 hospitals) certified by the Japanese Society of Neurology and/or Japan Stroke Society in 2016. This study consisted of a two-step survey; patients with CADASIL were identified genetically by the first questionnaire, and their clinical features were assessed by the second questionnaire. Selected 6 hospitals registered the data of all CADASIL patients using a Research Electronic Data Capture (REDCap) system for the second questionnaire. Results Based on the criteria, 88 patients (50 male and 38 female) with CADASIL were enrolled. The mean age of symptom onset was 49.5 years. Sixteen (18.2%) patients had an elderly onset (> 60 years). Thirteen patients (13.6%) had history of migraine with aura and 33 patients (37.5%) had vascular risk factor(s). From among the 86 patients who were examined using magnetic resonance imaging, abnormal deep white matter lesions were detected in 85 patients (98.8%), WMLs extending to anterior temporal pole in 73 patients (84.9%), and cerebral microbleeds in 41 patients (47.7%). Anti-platelet therapy was received by 65 patients (73.9%). Thirty-eight patients (43.2%) underwent treatment with lomerizine hydrochloride. Thirty-four different mutations of NOTCH3 were found in exons 2, 3, 4, 5, 6, 8, 11, 14, and 19. Most of the mutations existed in exon 4 (n= 44, 60.3%). The prevalence rate of CADASIL was 1.20 to 3.58 per 100,000 adults in Japan. Conclusions This questionnaire-based study revealed clinical features and treatment status in Japanese CADASIL patient, although it may not be an exhaustive search. We have constructed the REDCap database for these CADASIL patients.